Changes in the electron paramagnetic resonance spectra of albumin-associated spin-labeled stearic acid as a diagnostic parameter of colorectal cancer - Liu, Zhongchao (BioMed Central, 2013)
BACKGROUND: With more than 940,000 new colorectal cancer cases worldwide each year, there is no better way for colorectal cancer routine screening. The aim of this study was to investigate whether the fatty acid binding to albumin is detectably and significantly altered in colorectal cancer patients when compared with healthy people, in order to find a better way for colorectal cancer diagnosis. METHODS: One hundred and forty-one patients operatively treated for colorectal cancer were included in the examination, and 180 healthy people were also enrolled as controls. Commercial 16-doxyl stearic acid was used as spin probe. Serum albumin was analyzed by electron paramagnetic resonance (EPR) with spin probe. Discriminant analysis was carried out using the measured EPR spectra by SPSS 20.0. RESULTS: Of the original grouped cases, 89.4% were correctly classified. Of the cross-validated grouped cases, 86.9% were correctly classified. Using Fisher linear discriminant analysis we were able to develop a mathematical model allowing for identification of colorectal cancer patients based on five values (both relative intensity and peak width) which are obtained from the EPR spectrum. CONCLUSIONS: Cancer-associated alterations to albumin can be assessed by spin-label EPR. The potential applications for this diagnostic technique are significant and represent a cost-effective means for screening patients with cancer. Spin probe for diagnosis of colorectal cancer might be a useful tool and further studies should take place in order to investigate all stages of colorectal cancer patients.